2015
DOI: 10.1186/s13620-016-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Typhlocolitis associated with Clostridium difficile ribotypes 078 and 110 in neonatal piglets from a commercial Irish pig herd

Abstract: Background Clostridium difficile is a recognised cause of typhlocolitis and diarrhoea in neonatal pigs but has never been confirmed in association with pathology and disease in Irish pigs.Case PresentationFour neonatal piglets, with a history of diarrhoea were referred to the Central Veterinary Research Laboratory, Backweston for necropsy. They were from a fully integrated, commercial pig farm with approximately 1000 sows. Three piglets had acute, superficial, erosive and suppurative typhlocolitis and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We have reported C. difficile ribotype 078 in cases of typhlocolitis in neonatal piglets in Ireland (9), and Knetsch et al found that ribotype 078 isolates carried by farmers in the Netherlands and their pigs were identical by whole-genome sequence analysis (10). These findings suggest that C. difficile isolates might be shared between humans and pigs when in close proximity.…”
Section: Human and Porcine Transmission Of Clostridioides Diffi Cile Ribotype 078 Europementioning
confidence: 64%
See 1 more Smart Citation
“…We have reported C. difficile ribotype 078 in cases of typhlocolitis in neonatal piglets in Ireland (9), and Knetsch et al found that ribotype 078 isolates carried by farmers in the Netherlands and their pigs were identical by whole-genome sequence analysis (10). These findings suggest that C. difficile isolates might be shared between humans and pigs when in close proximity.…”
Section: Human and Porcine Transmission Of Clostridioides Diffi Cile Ribotype 078 Europementioning
confidence: 64%
“…The porcine isolates from Ireland in this analysis were from available samples processed at the CVRL. These isolates included samples from neonatal piglets that had typhlocolitis (9). We have identified genomic similarities among isolates causing human and veterinary infections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that C. difficile can cause enteritis in neonatal piglets [ 27 29 ], but epidemiologic studies do not support the idea of C. difficile being a primary diarrhoeic pathogen in pigs [ 4 , 13 , 30 32 ]. In accordance with this, the detection of C. difficile was not associated with being a case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that C. difficile could be an etiological agent of enteritis in neonatal piglets [ 90 , 91 , 92 ]. While it is not considered to be a primary diarrheic pathogen in pigs based on epidemiological studies [ 93 , 94 , 95 , 96 ], other studies indicate that C. difficile is an emerging pathogen in neonatal diarrhoea [ 1 , 97 , 98 ]. These findings highlight the need for farmers to use recently developed commercial vaccines that provide immunization against C. difficile to sows to prevent neonatal diarrhoea via passive immunity.…”
Section: Discussionmentioning
confidence: 99%